Study of SWOT Analysis on Academic Information System at Universitas Pattimura Ambon - Atiana Sofia Kaci; Dwi Arman Prasetya; Ninik Sisharini (Fakultas Teknik Universitas Bhayangkara, 2017)
At this time, every organization try to implement the system or information technologies in order to improve theefficiency and effectiveness of in the process of business, also to be able to give the added value in the form ofcompetiteve advantage in the business competition. The application of information technologies system will behelpful if the implementation is in accordance with the goal, vision and mission of the organization to establish abusiness strategy and a strategy of the information technology system. So that it takes analysis of the many factorsthat influence the formation of a planning a strategy of the system or information technologies are able to adapt andin harmony with a strategy of business. One of the techniques in analyzing strategy is to use analysis SWOT where the analysis focusing to Strength, Weakness, Opportunity, and Threat